Incremental Quail Farming Business and Switching Value in Business Development (Case Study: Integrated Waste Disposal Site in Bogor City) - Adriyanto, Farell Reza; Rosiana, Nia (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Quail birds are considered one of the poultry commodities in the livestock sector. There is an imbalance between the supply and demand of quail eggs. The quail farm located at the integrated waste disposal site in Bogor City aims to increase its quail egg-laying capacity by 25 percent, with requires an investment. This study aims to analyze the feasibility of developing a quail farm at the Integrated Waste Disposal Site in Bogor City. The feasibility analysis encompasses both non-financial and financial aspects. The results of the non-financial aspect analysis indicate that the planned farm development is viable for implementation, as the feasibility scores for each non-financial aspect exceed 50 percent. The financial analysis, without development, yields an NPV of IDR 232,229,923, an IRR of 21 percent, a Net B/C of 2.04, and a Payback Period of 7 years and 5 months. On the other hand, the financial analysis, with development, yields an NPV of IDR 662,445,448, an IRR of 44 percent, a Net B/C of 3.80, and a Payback Period of 3 years and 9 months. Therefore, under both conditions, the business development plan is financially feasible. Additionally, there is an increase in net benefits of 53.15 percent with the development. Based on the switching value analysis, the farm is sensitive to a decline in income.